DeepT3_4: A Hybrid Deep Neural Network Model for the Distinction Between Bacterial Type III and IV Secreted Effectors - Yu, Lezheng; Liu, Fengjuan; Li, Yizhou; Luo, Jiesi; Jing, Runyu (Frontiers in Microbiology, 2021)
Gram-negative bacteria can deliver secreted proteins (also known as secreted effectors) directly into host cells through type III, IV, VI secretion systems and cause various diseases. These secreted effectors are heavily involved in the interactions between bacteria and host cells, so their identification is crucial for the discovery and development of novel anti-bacterial drugs. It is currently challenging to accurately distinguish type III secreted effectors (T3SEs) and type IV secreted effectors (T4SEs) because neither T3SEs nor T4SEs contain N-terminal signal peptides, and some of these effectors have similar evolutionary conserved profiles and sequence motifs. To address this challenge, we develop a deep learning approach called DeepT3_4 to correctly classify T3SEs and T4SEs. We generate amino-acid character dictionary and sequence-based features extracted from effector proteins and subsequently implement these features into a hybrid model that integrates recurrent neural networks (RNNs) and deep neural networks (DNNs). After training the model, the hybrid neural network classifies secreted effectors into two different classes with an accuracy, F-value and recall of over 80.0%. Our approach stands for the first deep learning approach for the classification of T3SEs and T4SEs, providing a promising supplementary tool for further secretome studies.